EFFICIENCY OF MUTUAL FUND SCHEMES DURING COVID-19: EMPIRICAL ANALYSIS IN INDIAN CONTEXT USING DEA APPROACH - Kaur, Dr. Manpreet; Sandhu, Akasha (The journal of contemporary issues in business and government, 2022)
The disruptions created by COVID-19 has lasting implications on the countries across the world. Apart from impacting key sectors of the economy, COVID has significantly affected the financial sector causing volatility and changes in asset valuation. There is no doubt that mutual funds still remain the popular mode of investment during COVID-19 followed by equities. However, shrinking fees, reducing profit margins and ever-changing investors preferences along with the pandemic imposed new set of challenges for the fund managers. Using data envelopment analysis, this paper examines the efficiency of open- ended equity funds and select debt schemes during COVID-19. The analysis reveals that during COVID, equity schemes pertaining to large and multi-cap segment were efficient. But the efficiency of mid and small cap equity schemes was affected due to the high expenses’ ratio and volatility. Interestingly, all open-ended debt schemes were efficient during COVID with mean efficiency score more than equity schemes. As no single fund house is found to be efficient in all the segments, the investor can pick efficient schemes to construct optimum portfolio of mutual funds.